(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Parkinson’s disease (PD) is common neurological illness of geriatric population having cardinal motor features like bradykinesia, asymmetrical resting tremors and rigidity. However it is also associated with certain non-motor symptoms (NMS) which are considered as part of PD. NMS may include urinary symptoms, forgetfulness, gastrointestinal symptoms and skin manifestations and many more with variable frequency and intensity. Objective: The main objective of study was to find frequency of NMS among patients of PD already taking medications for it. Material and Methods: This cross-sectional study was done at Neurology department, Fatima Jinnah Medical University/Sir Ganga Ram Hospital, Lahore (FJMU/SGRH) over duration of 1 year from July, 2015 to June, 2016. All the patients already diagnosed with PD and taking treatment for it, were enrolled in study. The Demographic details were assessed. They were specifically asked for NMS by a questionnaire formulated by authors. All the data were analyzed through SPSS version 20. Results: A total 131 patients were recruited in the study. The mean age of patients was calculated as 58.87 ± 9.45 years. Most of the patients in this study were males which were 64.1% (n=84). The most common symptom found in this study was impaired concentration among 78 participants (59.5%) followed by Sialorrhea in 74 patients (56.4%) , unexplained pain in 69 patients (52.6%), Nocturia (54.1%), urinary urgency (51.1%) and Hyposmia (46.5%). Other NMS symptoms were present with lower frequencies. Conclusion: We conclude that NMS are quite prevalent in patients with PD in our setup , hence they must be specially taken care when dealing with PD. We also need to educate our patients regarding the presence of these symptoms and physicians to manage them promptly.